2004
DOI: 10.1056/nejmoa031918
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Prostate Cancer among Men with a Prostate-Specific Antigen Level ≤4.0 ng per Milliliter

Abstract: Biopsy-detected prostate cancer, including high-grade cancers, is not rare among men with PSA levels of 4.0 ng per milliliter or less--levels generally thought to be in the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
1,251
5
68

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,167 publications
(1,353 citation statements)
references
References 29 publications
29
1,251
5
68
Order By: Relevance
“…However, Kundu et al did not compare the relative accuracy of PSAD and PSA in predicting these pathological and clinical findings. 13 Jones et al recently reported that PSAD was significantly associated with patient age, prostate weight, cancer volume, Gleason score, and positive SM rates. Furthermore, PSAD was also found to be an independent predictor of biochemical recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kundu et al did not compare the relative accuracy of PSAD and PSA in predicting these pathological and clinical findings. 13 Jones et al recently reported that PSAD was significantly associated with patient age, prostate weight, cancer volume, Gleason score, and positive SM rates. Furthermore, PSAD was also found to be an independent predictor of biochemical recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that our results demonstrate a very small increase in the predictive accuracy of PSAD among patients with biopsy Gleason score ≤ 6 is consistent with knowledge that patients with lower grade prostate cancer generally exhibit lower PSA levels, thus reducing the predictive value of PSA in this subgroup. 13 Kundu et al recently demonstrated that measurement of PSAD was useful for determining the aggressiveness of prostate cancer. Specifically, PSAD was associated with positive SM rates, prostatectomy Gleason score, cancer volume, PSA velocity in the year prior to diagnosis, and biochemical recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…PSA testing is very sensitive, but two-thirds of PSA elevations are caused by non-malignant prostate disorders [1] and widespread PSA screening resulted in the detection of clinically insignificant PCA [2]. On the other hand, a number of high grade PCA are overlooked because patients' PSA levels are within normal range [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is no established PSA cut point for detecting prostate cancer with simultaneously high sensitivity and high specificity, but there is a continuum of prostate cancer risk at all values, with higher values of PSA having been associated with higher risk. 25,26 Of the prostate cancers diagnosed in 2010, 12.5% had PSA values 4.0 ng/ml, that is, they had values in the range usually considered "normal" (Table 6). Of these, 49.9% had a clinical interpretation of positive.…”
Section: Discussionmentioning
confidence: 99%